Step1:- Decide initial values for x1 & x2 & stopping criteria, E.
Step2:- Compute f1 = f ( x1 ) & f2 = f ( x2 ).
Step3:- If ( f1 * f2) > 0, x1 & x2 do not bracket any root & go to step 7.
Otherwise continue.
Step4:- Compute x0 = ( x2 - x1 ) / x2 & compute f0 = f ( x0 ).
Step5:- If ( f1 = f0 ) < 0 then
Set x2 = x0
else
Set x1 = x0
Set f1 = f0
Step6:- If absolute value of ( x2 - x1 ) / x2 is less than error E, then
root = ( x2 - x1 ) / 2
write the value of root
go to step 7.
else
go to step 4.
Step7:- Stop.
Step2:- Compute f1 = f ( x1 ) & f2 = f ( x2 ).
Step3:- If ( f1 * f2) > 0, x1 & x2 do not bracket any root & go to step 7.
Otherwise continue.
Step4:- Compute x0 = ( x2 - x1 ) / x2 & compute f0 = f ( x0 ).
Step5:- If ( f1 = f0 ) < 0 then
Set x2 = x0
else
Set x1 = x0
Set f1 = f0
Step6:- If absolute value of ( x2 - x1 ) / x2 is less than error E, then
root = ( x2 - x1 ) / 2
write the value of root
go to step 7.
else
go to step 4.
Step7:- Stop.